Computer Vision-Based Portable System for Nitroaromatics Discrimination. (29th June 2016) - López-Ruiz, Nuria; Erenas, Miguel M.; de Orbe-Payá, Ignacio; Capitán-Vallvey, Luis F.; Palma, Alberto J.; Martínez-Olmos, Antonio
Abstract : A computer vision-based portable measurement system is presented in this report. The system is based on a compact reader unit composed of a microcamera and a Raspberry Pi board as control unit. This reader can acquire and process images of a sensor array formed by four nonselective sensing chemistries. Processing these array images it is possible to identify and quantify eight different nitroaromatic compounds (both explosives and related compounds) by using chromatic coordinates of a color space. The system is also capable of sending the obtained information after the processing by a WiFi link to a smartphone in order to present the analysis result to the final user. The identification and quantification algorithm programmed in the Raspberry board is easy and quick enough to allow real time analysis. Nitroaromatic compounds analyzed in the range of mg/L were picric acid, 2, 4-dinitrotoluene (2, 4-DNT), 1, 3-dinitrobenzene (1, 3-DNB), 3, 5-dinitrobenzonitrile (3, 5-DNBN), 2-chloro-3, 5-dinitrobenzotrifluoride (2-C-3, 5-DNBF), 1, 3, 5-trinitrobenzene (TNB), 2, 4, 6-trinitrotoluene (TNT), and tetryl (TT).